Who is energy poor? Evidence from the least developed regions in China. (February 2020) - Jiang, Lu; Yu, Lu; Xue, Bing; Chen, Xingpeng; Mi, Zhifu
Abstract: Energy poverty has become one of the major challenges faced by the world's energy system. However, there is no consensus on the measure of energy poverty. Several approaches have been proposed, among which the energy poverty line has been defined as the minimum quantity of energy required for basic life, particularly for cooking and heating. This paper estimates the relationship between energy expenditure and household income and identifies the energy poverty line based on the threshold above which the energy share becomes insensitive to household income using household survey data from rural Qinghai, China. Considering the ongoing energy transition and the negative impacts of biomass energy consumption for the environment and health, the study sets a scenario in which all bioenergy consumption is replaced with electricity. The findings show that 57% of rural households in rural Qinghai are energy poor. The phase of energy poverty in terms of basic energy access has passed, so increasing the share of efficient modern energy in household energy consumption requires more attention. Considering the existence of a population that is not income poor but is energy poor, a conventional policy design that primarily targets income-poor households may be inappropriate in this case. Highlights: We provide an approach to estimate energy poverty tailored to local specificities. The energy poverty lines are identified based on different scenarios. About 57% of rural households are energy poor in rural Qinghai, China. Increasing the share of modern energy is key to reducing household energy poverty.